New records of fishes for Trindade-Martin Vaz oceanic insular complex, Brazil - Pinheiro, Hudson T.; Camilato, Victor; Gasparini, João Luiz; Joyeux, Jean-Christophe (Zootaxa, 2009)
Thirty-two new records for shore fishes were made at the Trindade-Martin Vaz oceanic insular complex, located 1,160 km off the Brazilian coast. These records are related to an increase in sampling effort and to temporal variation in population size. Newly found but very abundant species hypothetically exemplify temporal variations in population size. The Vitória-Trindade submarine chain also may function as a series of stepping-stones facilitating transport of typically coastal species. The new records reveal a lack of knowledge of the fish fauna of this unique location. Studies aimed at the exploration of shallow areas, deep reefs and seamounts of the Vitória-Trindade chain, aided by ichthyoplanktonic surveys, are essential to a better understanding of the fish community and the processes of colonization in this oceanic locality.